Trainer Kit Tegangan Langkah Berbasis Arus Gangguan sebagai Media Pembelajaran Sistem Pembumian - Anton Firmansyah; Andri Suyadi; Indah Susanti; Muhammad Noer; Siti Khofifah; Nabila Shada (Politeknik Negeri Malang, 2026)
Human safety and electrical equipment reliability in power installations are strongly influenced by step voltage generated by fault currents flowing into the ground. The resulting ground potential distribution, which depends on fault current magnitude, grounding system characteristics, soil resistivity, and distance from the fault point, determines the level of electrical hazard to humans. This study aims to design, develop, and evaluate a step voltage trainer kit based on fault current injection as a practical learning media for understanding grounding system behavior and electrical safety principles. The research methodology involved field measurement of grounding electrode resistance, calculation of soil resistivity, design and fabrication of the trainer kit, and experimental testing under various fault current levels and measurement distances, both with and without a grounding system. Experimental results indicate that step voltage reaches its maximum value at locations closest to the fault point and decreases significantly with increasing distance, while the measured fault current remains relatively stable across different distances. The application of a low-resistance grounding system effectively reduces step voltage and flattens the ground potential gradient, thereby mitigating electrical hazard risks. The integration of field-based grounding resistance data into the soil simulator enables the trainer kit to realistically represent actual installation conditions. These findings demonstrate that the developed step voltage trainer kit provides a reliable, empirical, and safe educational platform for visualizing the relationship between fault current, soil resistivity, grounding systems, and step voltage hazards in electrical power installations.